题目内容
(1)计算:
+(-
)+
+(-
)+(-
)
(2)计算:(-2)4÷(-2
)2+5
×(-
)-0.25
(3)先化简,再求:(2a2-5a)-2(3a+5+a2)的值,其中a=-1
(4)解方程:1-
=2-
.
1 |
2 |
2 |
3 |
4 |
7 |
1 |
2 |
1 |
3 |
(2)计算:(-2)4÷(-2
2 |
3 |
1 |
2 |
1 |
6 |
(3)先化简,再求:(2a2-5a)-2(3a+5+a2)的值,其中a=-1
(4)解方程:1-
x-1 |
2 |
x+2 |
3 |
(1)
+(-
)+
+(-
)+(-
)
=(
-
)+(-
-
)+
=0-1+
=-
;
(2)(-2)4÷(-2
)2+5
×(-
)-0.25
=16÷
-
-
=2
-
-
=2-
=1
;
(3)(2a2-5a)-2(3a+5+a2)
=2a2-5a-6a-10-2a2
=-11a-10
当a=-1时,原式=11-10=1;
(4)1-
=2-
,
6-3(x-1)=12-2(x+2),
6-3x+3=12-2x-4,
-x=-1,
x=1.
1 |
2 |
2 |
3 |
4 |
7 |
1 |
2 |
1 |
3 |
=(
1 |
2 |
1 |
2 |
2 |
3 |
1 |
3 |
4 |
7 |
=0-1+
4 |
7 |
=-
3 |
7 |
(2)(-2)4÷(-2
2 |
3 |
1 |
2 |
1 |
6 |
=16÷
64 |
9 |
11 |
12 |
1 |
4 |
=2
1 |
4 |
1 |
4 |
11 |
12 |
=2-
11 |
12 |
=1
1 |
12 |
(3)(2a2-5a)-2(3a+5+a2)
=2a2-5a-6a-10-2a2
=-11a-10
当a=-1时,原式=11-10=1;
(4)1-
x-1 |
2 |
x+2 |
3 |
6-3(x-1)=12-2(x+2),
6-3x+3=12-2x-4,
-x=-1,
x=1.
![](http://thumb.zyjl.cn/images/loading.gif)
练习册系列答案
相关题目